The Essence Of The Concept Of Freedom In Law - Soliboyev Umidbek (International Journal on Orange Technologies, 2021)
In our article, the role of law in human nature. Principles of different understanding of the concept of freedom in law. Historical manifestations of freedom, reflections on the freedom of existence in practice